PLC-Based adaptive controller for stability tank pressure - Pham, Trong Tuong; Le, Ngoc Binh; Pham, Huy Hoang; Tran, Thi Linh Nhi; Ta , Van Phuong (Journal of Technical Education Science, 2019)
In recent years, the trend of applying intelligent controllers into an industrial system has been gaining more and more attention. Artificial neural networks is a must to mention when mentioning intelligent controllers. Not only for it’s good performance but also for it’s wide range of application. With an adaptive controller, we can save time of recalibrating the controller when load changes. This paper confirms the practical effect of applying Artificial Neural Networks (ANNs) using Radial basis function (RBF) bases on Sliding mode control (SMC) to control nonlinear systems. The proposed algorithm is put into comparison with the super twisting 2-SMC, which was designed to reduce chattering and increase the performance of conventional SMC. The pressure system is controlled by a Programmable Logic Controller (PLC), which is the most commonly used in industry, with a view to applying intelligent controllers in industrial applications to increase quality, productivity and reduce downtime of current systems.